Movilidad y accesibilidad en el Gran Resistencia. Principales problemas y desafíos - Alcalá, Laura (2015)
In the past 30 years, the Greater Resistencia has become a metropolitan area closely related to the city of Corrientes, changing its territorial scale and intensity of functions. Mobility is one of the indicators where the cross-functional relationship between the municipalities is better expressed. In addition to the increase in commuting, you also have the problem of unequal conditions of connectivity and accessibility, the presence of architectural barriers, the lack of certain forms of public transport alternatives, and the high overall cost of this adds. These conditions, in addition to the economic vulnerability of a wide part of the society, has led to the widespread use of the motorcycle, exacerbating conflicts and increasing traffic accident rates. However, Resistencia offers highly favorable infrastructural conditions for reversing these problems. For example, the widths of streets and avenues, the regularity of the avenues, etc. The topographical conditions and the scale give an advantage to the use of public transport and cycling as other option.